2021
DOI: 10.1111/all.15039
|View full text |Cite
|
Sign up to set email alerts
|

The bile acid‐activated retinoic acid response in dendritic cells is involved in food allergen sensitization

Abstract: Background: Alteration of commensal microbiota is highly correlated with the prevalence of allergic reactions to food in the gastrointestinal tract. The mechanisms by which microbiota modulate food allergen sensitization in the mucosal site are not fully understood. Methods: We generate DCs specific knockout of retinoic acid receptor α (Rara) gene mice (DC KO Rara) to evaluate food sensitization. The bile acid-activated retinoic acid response was evaluated by flow cytometry, real-time RT-PCR and Illumina trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…Bacterial modified secondary bile acids, such as deoxycholic acid and lithocholic acid, are FXR agonists, while supernatants from in vitro bacterial cultures also possess FXR ligands 178,179 . FXR‐RARα signalling in murine mucosal dendritic cells supported food allergen‐specific IgE and IgG1 production, while allergic diarrhoea can be attenuated by FXR agonists due to their antisecretory effects in colonic epithelial cells 180,181 . Ursodeoxycholic acid treatment of OVA‐sensitized mice prior to OVA aerosol challenge significantly reduced eosinophilic airway inflammation via FXR signalling in dendritic cells 182 .…”
Section: Nuclear Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial modified secondary bile acids, such as deoxycholic acid and lithocholic acid, are FXR agonists, while supernatants from in vitro bacterial cultures also possess FXR ligands 178,179 . FXR‐RARα signalling in murine mucosal dendritic cells supported food allergen‐specific IgE and IgG1 production, while allergic diarrhoea can be attenuated by FXR agonists due to their antisecretory effects in colonic epithelial cells 180,181 . Ursodeoxycholic acid treatment of OVA‐sensitized mice prior to OVA aerosol challenge significantly reduced eosinophilic airway inflammation via FXR signalling in dendritic cells 182 .…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“… 178 , 179 FXR‐RARα signalling in murine mucosal dendritic cells supported food allergen‐specific IgE and IgG1 production, while allergic diarrhoea can be attenuated by FXR agonists due to their antisecretory effects in colonic epithelial cells. 180 , 181 Ursodeoxycholic acid treatment of OVA‐sensitized mice prior to OVA aerosol challenge significantly reduced eosinophilic airway inflammation via FXR signalling in dendritic cells. 182 Similarly, the FXR ligand chenodeoxycholic acid attenuates murine allergic airway inflammation by inhibiting TH2 cytokine secretion.…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…Secondary bile acids have also been demonstrated to induce the expression of the transcription factor Foxp3, as well as the production of RORγ+ regulatory T-cells [ 98 , 99 , 100 ]. A recent study demonstrated a mechanism of food sensitization via bile acid-mediated activation of retinoic acid responsive element in dendritic cells, thereby promoting food-allergen specific IgE and IgG1 [ 101 ]. The role of bile acids in regulating immunological and inflammatory responses is complex, and continued studies will help elucidate their role in the development of therapeutic approaches to food allergies.…”
Section: Metabolitesmentioning
confidence: 99%
“…Considering that low vitamin D is related to the development of food allergy ( 57 ), the mechanism of which is involved with ILCs ( 58 ), the balance between vitamins A and D might be an important factor in the ILCs-related diseases like IBD. Meanwhile, gut-dysbiosis-induced dysregulated bile acids (BAs) induce enhancement of RA signaling in mucosal DCs, leading to food allergen-specific IgE and IgG1 ( 59 ), implying that BA-RA signaling may change Th2 cells prime DCs.…”
Section: Introductionmentioning
confidence: 99%